Extraction of γ at LHCb with a combined Bs →d s ±K∓ and Bd → D±π∓ analysis - Wilkinson, G (2005)
A combined analysis of the CP violating observables in the channels B →Ds±K∓ and B d→ D± π∓ allows the CKM angle γ to be determined in a manner which has certain advantages over the analysis of each channel separately. In particular, the combined analysis reduces greatly the number of ambiguous solutions which would otherwise be present. The potential of the method is illustrated using the expected performance of the LHCb experiment.